Basic journalism an ASEAN handbook - Santos, Vergel O. (V. O. Santos], 1992)
A handbook designed for learners and new practitioners of English-language journalism in ASEAN, Southeast Asia's predominantly Malay-Chinese community of nations. It attempts to reconcile to native realities the philosophies and traditions on which journalism is founded, and in that context offers specific advice on the range of editorial skills that makes a basically well-rounded newspaper practitioner.